Upaya Peningkatan Kedisiplinan Siswa melalui Pembelajaran Pendidikan Agama Islam di SMK Ma’arif 4 Kawedusan Kebumen - Syukron Makmun (LPPM Institut Agam Islam Nahdlatul Ulama (IAINU) Kebumen, 2022)
The aim of the research to tell the efforts are made through the learning of Islamic Educational to improve the discipline of students in SMK MA’ARIF 4 Kawedusan Kebumen. This research is qualitative research whose data in the form of statements and documents. This research used a naturalistic approach to researching where natural (natural setting) and field (Field Research), to obtain the required data information researchers used the method of observation, interviews, and documentation. Analysis of the data is used in the form of triangulation analysis that includes data reduction, data presentation, and conclusion. The result of this research is found: 1) the discipline of students of SMK MA’ARIF 4 Kawedusan Kebumen has been good enough even though there are those who violate the rules. It still need to improve and reform the discipline of students so that they understand what is wrong even a little infractions. 2) The efforts of teacher to improve discipline students use the rules. For example, when there is student break the rule of school, especially PAI's teachers have to follow up violations that done by learners to give direction, motivation, giving punishment, or reward that is commensurate to what which is conducted.